The spatial distribution of liquid film thickness outside the horizontal falling film tube. (November 2019) - Lin, Shi; Liu, Xi; Li, Xuelai
Highlights: Visualization of the spatial distribution of film thickness variation in 3D is obtained. The spatial distribution rule of heat transfer coefficient is the same as that of film thickness. The hazardous area where thinnest film or worst heat transfer performance exits is obtained. The change path of the minimum thickness is a space curve rather than a plane curve. Abstract: The visualization method in 3D simulation is established to investigate the spatial distribution of film thickness and local heat transfer coefficient to avoid the dryout phenomenon and improve the heat transfer performance. The simulated results are in good agreement with the experimental data in the literature. The results indicate that the spatial distribution of liquid film is peak-valley-peak, and there exists a minimum thickness. The change path of the hazardous area is a space curve rather than a plane curve. The film thickness with dimensionless axial length of 0.375 is closest to the average film thickness. The hazardous area approaches the inlet column as the tube diameter increases in the axial direction. The tube diameter has a great influence on the hazardous area, and the large tube diameter promotes it to move to the inlet column. The spatial distribution rule of the local heat transfer coefficient is the same as that of film thickness. The place with the worst heat transfer performance is approximately in the same position as the place with the thinnest liquid film. The results provide a good guidance for further study on falling film process.